Clinical Utility of Medical Exome Sequencing: Expanded Carrier Screening for Patients Seeking Assisted Reproductive Technology in China - Tong, Keya; He, Wenbin; He, Yao; Li, Xiurong; Hu, Liang; Hu, Hao; Lu, Guangxiu; Lin, Ge; Dong, Chang; Zhang, Victor Wei; Du, Juan; Liu, Dongyun (Frontiers in Genetics, 2022)
Abstract Purpose: Expanded carrier screening (ECS) is an effective method to identify at-risk couples (ARCs) and avoid birth defects. This study aimed to reveal the carrier spectrum in the Chinese population and to delineate an expanded carrier gene panel suitable in China. Methods: Medical exome sequencing (MES), including 4158 disease-causing genes, was offered to couples in two reproductive centers. MES was firstly used as a diagnostic yield for potential patients and then was employed to perform ECS. Clinical information and ECS results were retrospectively collected. Results: A total of 2234 couples, representing 4468 individuals receive MES. 254 individuals showed suspicious genetic disease symptoms, and 56 of them were diagnosed by MES. Overall, 94.5% of them were carriers of at least one disease-causing variant. The most prevalent genes were GJB2 for autosomal recessive diseases, G6PD for X-linked diseases. At-risk couple (ARC) rate was 9.80%, and couples were inclined to receive preimplantation genetic testing (PGT) when diseases were classified as ‘profound’ or ‘severe’. Conclusion: The study brought insight to establish a suitable ECS gene panel for Chinese population. Disease severity significantly influenced reproductive decision-making. The results highlighted the necessity of conducting ECS for couples before assisted reproductive technology (ART).